Campus Safety Riding: Establishing A Safe Campus Traffic Zone - Eti Rimawati; Bayu Yoni Setyo Nugroho; Ririn Nurmandhani; Tiara Fani; Suhat; Asma Khalid (CV Media Inti Teknologi, 2025)
Traffic-related accidents involving university students, particularly those aged 18–25, have become a growing concern in Indonesia, with many incidents occurring due to inadequate infrastructure and lack of traffic discipline in densely populated campus environments. This community service program was initiated by Universitas Dian Nuswantoro (UDINUS) in Semarang to address these challenges through the establishment of a “Campus Safety Riding Zone.” The program aimed to increase road safety awareness, promote safe behavior among students and residents, and improve campus-area traffic infrastructure. Activities included coordination with local authorities, painting red-marked safe zones and zebra crossings, installing speed limit signs (30 km/h), and distributing an educational pocketbook titled “Crossing Etiquette on Campus” The intervention area, located on Nakula I Street, was selected due to its high traffic volume between the subdistrict office and UDINUS Building A. Post-intervention observations indicated that drivers generally reduced their speed when entering the safety zone, although issues like improper parking persisted. The initiative demonstrated that a combination of infrastructure enhancement, community education, and multi-stakeholder collaboration can effectively foster a safer traffic culture in university environments. This model offers a replicable framework for other higher education institutions to support student and pedestrian safety through community-based strategies.